Trichomycterus pauciradiatus, a new catfish species from the upper rio Paraná basin, southeastern Brazil (Siluriformes: Trichomycteridae) - Alencar, Aline R.; Costa, Wilson J.e.m. (Zootaxa, 2006)
Trichomycterus pauciradiatus, new species, is described from the rio Paraná basin, southeastern Brazil. It differs from all other species of Trichomycterus by having four pelvic-fin rays. The new species is possibly closely related to T. reinhardti (Eigenmann, 1918), since both share a unique color pattern consisting of a yellow body with a broad dark brown stripe along the lateral midline.  The stripe is bordered dorsally by a longitudinal bright yellow zone lacking dark chromatophores.